Identification of phlebotomine sand flies (Diptera: Psychodidae) by matrix-assisted laser desorption/ionization time of flight mass spectrometry - Vit Dvorak; Petr Halada; Kristyna Hlavackova; Emmanouil Dokianakis; Maria Antoniou; Petr Volf (Parasites & Vectors, 2014)
Abstract Background Phlebotomine sand flies are incriminated in the transmission of several human and veterinary pathogens. To elucidate their role as vectors, proper species identification is crucial. Since traditional morphological determination is based on minute and often dubious characteristics on their head and genitalia, which require certain expertise and may be damaged in the field-collected material, there is a demand for rapid, simple and cost-effective molecular approaches. Methods Six laboratory-reared colonies of phlebotomine sand flies belonging to five species and four subgenera (Phlebotomus, Paraphlebotomus, Larroussius, Adlerius) were used to evaluate the discriminatory power of matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS). Various storage conditions and treatments, including the homogenization in either distilled water or given concentrations of formic acid, were tested on samples of both sexes. Results Specimens of all five analysed sand fly species produced informative, reproducible and species-specific protein spectra that enabled their conclusive species identification. The method also distinguished between two P. sergenti colonies originating from different geographical localities. Protein profiles within a species were similar for specimens of both sexes. Tested conditions of specimen storage and sample preparation give ground to a standard protocol that is generally applicable on analyzed sand fly specimens. Conclusions Species identification of sand flies by MALDI-TOF MS is feasible and represents a novel promising tool to improve biological and epidemiological studies on these medically important insects.